2001
DOI: 10.1039/b100247n
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and reaction of HOI and IONO2 on frozen and dry NaCl/NaBr surfaces and H2SO4

Abstract: The uptake and reaction of HOI and with dry and frozen NaCl/NaBr salt surfaces was investigated IONO 2 using a coated-wall Ñow tube reactor coupled to a mass spectrometer for gas-phase analysis. HOI and IONO 2 react with both surfaces to form the di-halogens IBr and ICl, which are released into the gas phase. On mixed Cl~/Br~surfaces in which the concentration of Cl~greatly exceeds that of Br~, both HOI and react IONO 2 to form ICl or IBr. ICl reacts further with Br~to form the observed gas-phase product, IBr.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 38 publications
6
61
1
Order By: Relevance
“…The results of and Holmes et al (2001) were obtained in different temperature ranges and concur that the uptake coefficient is large. A parameterisation, γ =7×10 −5 exp(1300/T ) generates uptake coefficients that are consistent with both datasets.…”
Section: Comments On Preferred Valuesmentioning
confidence: 85%
See 2 more Smart Citations
“…The results of and Holmes et al (2001) were obtained in different temperature ranges and concur that the uptake coefficient is large. A parameterisation, γ =7×10 −5 exp(1300/T ) generates uptake coefficients that are consistent with both datasets.…”
Section: Comments On Preferred Valuesmentioning
confidence: 85%
“…A parameterisation, γ =7×10 −5 exp(1300/T ) generates uptake coefficients that are consistent with both datasets. At the lower temperatures covered by , the uptake is observed to be irreversible, whereas Holmes et al (2001) observe partially reversible adsorption at 243 K. From the experimental datasets it is not obvious how HOI reacts with the ice surface. Both studies observed I 2 as product and Holmes et al (2001) suggest that this may arise from self-reaction of HOI (or reaction of HOI with IONO 2 impurity) on the ice surface.…”
Section: Comments On Preferred Valuesmentioning
confidence: 87%
See 1 more Smart Citation
“…Wachsmuth et al (2002) investigated uptake of HOBr on NaBr aerosol particles and found a mass accommodation coefficient of α = 0.6. Uptake of HOI on bromide has also been studied (Mössinger and Cox, 2001;Holmes et al, 2001). …”
Section: Laboratory Studiesmentioning
confidence: 99%
“…Several attempts have been made to measure BrO in the mbl outside the polar regions, both at a clean remote site (HAW99b-G) and also at sites that are more polluted to varying degrees (MHD96-G, MHD97a-G, MHD97b-G, MHD98-G, TEN97-G, WEY96a-G, WEY96b-G, CRT00-G). The results from these LP-DOAS measurements indicate ambient concentrations around or below the DL of the respective instruments (about 1 to 3 pmol/mol) (Alicke, 1997;Allan, 1998;Hönninger, 1999;.…”
Section: Inorganic Gas-phase Bromine Speciesmentioning
confidence: 99%